HISTOLOGICAL EFFECTS OF CITRUS AURANTIFOLIA ON GRAVID AND POST-PARTUM UTERUS - Ovwigho, Omunu Richard; Ebeye, Oladunni Abimbola; Brenmound, Jones-Dibie (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2023)
Diseases have afflicted man for ages but humans always make effort to remedy the situation in order to regain a life disturbed by these ailments. The earliest form of healing substances had been Traditional (herbal) medicines, but with the advent of civilization which had led to better scientific understanding of diseases and medications, orthodox medicines have become the main and well recognized products for the management of diseases in modern health systems. The aim of this study was to investigate the effects of citrus aurantifolia (lime plant) on gravid and non-gravid uterus of female wistar rats and their pups. A total of 50 Wistar rats were used in carrying out the experiment and classified into two Models. Each group in Model 1 contained 8 rats each, while in the Model 2, each group comprised 5 rats. The body weight of the rats were measured and recorded weekly. Group I-III in model 1 received 1ml/kg, 1.5 ml/kg and 2 ml/kg respectively, two rats from each group were euthanized at 7, 14 and 21 days to observe acute, subacute and chronic effect, group IV (control) received food and distilled water only. While in model 2, group I rats commenced 1 ml/kg of aqueous lime juice from the first day of gestation, group II received 1 ml/kg of aqueous lime 1week after gestation and group III were administered food and water. The histomorphological study of the uterus revealed deleterious effect of lime juice in a dose dependent pattern and Hormonal assay carried out showed a reduction in gonadotrophin level. In conclusion, high consumption of Lime juice compromises the outcome of pregnancy in the treated rats by the reduction in the crown rump length and weight of pups.